Being with God : the absurdity, necessity, and neurology of contemplative prayer - Sherrill, Andrew (Andrew Jeremy) (Grand Rapids: Brazos press, 2021)
"Pastor AJ Sherrill exposes the effects of living in a world full of noise and anxiety, showing us how quiet and contemplation are crucial not only for spiritual growth but also for mental health and helping us integrate practices of solitude into our daily lives"--
Includes bibliographical references.
Keywords: Contemplation; Prayer -- Christianity; Solitude -- Religious aspects -- Christianity; Spirituality -- Christianity